2016
DOI: 10.1002/lno.10367
|View full text |Cite
|
Sign up to set email alerts
|

Understanding marine dissolved organic matter production: Compositional insights from axenic cultures of Thalassiosira pseudonana

Abstract: Marine dissolved organic matter (DOM) is a key source of carbon and nutrients to microbial life in the oceans, but rapid biological utilization of labile DOM confounds its compositional characterization. In order to characterize potentially bioavailable DOM produced by phytoplankton, DOM from axenic cultures of Thalassiosira pseudonana cultivated in phosphorus (P) replete and low P conditions was extracted using high‐recovery electrodialysis (ED) techniques, which resulted in an average dissolved organic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 105 publications
2
26
0
Order By: Relevance
“…Thus, different biomes may harbour different hydrolytic potentials (Wietz et al, 2015). Furthermore, polysaccharides produced under phosphate limitation support a different microbial communities compared with polysaccharides produced under phosphate replete conditions (Saad et al, 2016). Accompanied with different microbial communities, polysaccharides exuded into phosphate-depleted conditions reveal a longer persistence if compared with nutrient replete conditions (Puddu et al, 2003).…”
Section: Role Of Algal Polysaccharides In Marine Carbon Cyclingmentioning
confidence: 99%
“…Thus, different biomes may harbour different hydrolytic potentials (Wietz et al, 2015). Furthermore, polysaccharides produced under phosphate limitation support a different microbial communities compared with polysaccharides produced under phosphate replete conditions (Saad et al, 2016). Accompanied with different microbial communities, polysaccharides exuded into phosphate-depleted conditions reveal a longer persistence if compared with nutrient replete conditions (Puddu et al, 2003).…”
Section: Role Of Algal Polysaccharides In Marine Carbon Cyclingmentioning
confidence: 99%
“…To our knowledge no direct evidence exists for DOM excretion related either assimilation or maintenance. However, DOM can be excreted from growing cells in the exponential phase of culture (Myklestad, 2000;Urbani et al, 2005;Lomas et al, 2000;Saad et al, 2016) and the specific DOM release is proportional to the specific growth rate (Myklestad et al, 1989;Underwood et al, 2004). Therefore, we assume that the growth flux contributes to DOM production at a specific rate…”
Section: Release Of Dissolved Organic Matter and Inorganic Nutrientsmentioning
confidence: 99%
“…Recent transcriptomic and genomic studies of marine plankton (Temperton et al 2011;Dyhrman et al 2012;Cruz de Carvalho et al 2016), and manipulative experiments with freshwater periphyton communities (Rier et al 2016) have further confirmed the ability of aquatic microbes to maintain significant polyP stores under acute P stress. Moreover, polyP appears to account for a significant fraction of the P pool even in P-replete environments, with quantitative estimates suggesting a contribution of around 10% of total P (Solrzano and Strickland 1968;Diaz et al 2008Diaz et al , 2016Orchard et al 2010;Young and Ingall 2010;Martin and Van Mooy 2013;Saad et al 2016). Laboratory culture experiments have confirmed that marine phytoplankton can have a high polyP content under a variety of culture conditions (Rhee 1973;Perry 1976).…”
mentioning
confidence: 99%